Extracellular vesicles from human-induced pluripotent stem cell-derived mesenchymal stromal cells (hiPSC-MSCs) protect against renal ischemia/reperfusion injury via delivering specificity protein (SP1) and transcriptional activating of sphingosine kinase - Yuan, X.; D. Li; X. Chen; Han, C.; L. Xu; Huang, T.; Dong, Z; Zhang, M. (Cell Death DisCell Death DisCell Death Dis, 2017)
Renal ischemia-reperfusion is a main cause of acute kidney injury (AKI), which is associated with high mortality. Here we show that extracellular vesicles (EVs) secreted from hiPSC-MSCs play a critical role in protection against renal I/R injury. hiPSC-MSCs-EVs can fuse with renal cells and deliver SP1 into target cells, subsequently active SK1 expression and increase S1P formation. Chromatin immunoprecipitation (ChIP) analyses and luciferase assay were used to confirm SP1 binds directly to the SK1 promoter region and promote promoter activity. Moreover, SP1 inhibition (MIT) or SK1 inhibition (SKI-II) completely abolished the renal protective effect of hiPSC-MSCs-EVs in rat I/R injury mode. However, pre-treatment of necroptosis inhibitor Nec-1 showed no difference with the administration of hiPSC-MSCs-EVs only. We then generated an SP1 knockout hiPSC-MSC cell line by CRISPR/Cas9 system and found that SP1 knockout failed to show the protective effect of hiPSC-MSCs-EVs unless restoring the level of SP1 by Ad-SP1 in vitro and in vivo. In conclusion, this study describes an anti-necroptosis effect of hiPSC-MSCs-EVs against renal I/R injury via delivering SP1 into target renal cells and intracellular activating the expression of SK1 and the generation of S1P. These findings suggest a novel mechanism for renal protection against I/R injury, and indicate a potential therapeutic approach for a variety of renal diseases and renal transplantation.
Keywords: Acute Kidney Injury/genetics/metabolism/pathology/*prevention & control; Animals; Apoptosis/genetics; Cell Differentiation; Cell Line, Transformed; Epithelial Cells/cytology/metabolism; Extracellular Vesicles/*chemistry; Gene Expression Regulation; Humans; Induced Pluripotent Stem Cells/cytology/metabolism; Kidney/metabolism/pathology; Lysophospholipids/metabolism; Male; Mesenchymal Stromal Cells/cytology/*secretion; Necrosis/genetics/metabolism/pathology/*prevention & control; Phosphotransferases (Alcohol Group Acceptor)/*genetics/metabolism; Rats; Rats, Sprague-Dawley; Reperfusion Injury/genetics/metabolism/pathology/*prevention & control; Signal Transduction; Sp1 Transcription Factor/deficiency/*genetics; Sphingosine/analogs & derivatives/metabolism